EFFECT OF FSH, PMSG ON SUPEROVULATO Y RESPONSE AND EMBRYO RECOVERY RATE IN TELLICHERRY GOATS
The mean onset of estrum was 26.18±0.70 and 17.85±0.44 h in the FSH and PMSG group, respectively. In the present study, the onset of estrum was significantly (P<0.0 1